Predictors of chlamydia or gonorrhea among people with HIV in Miami-Dade County Ryan White Program in 2017. Issue 5 (4th May 2022) - Gebrezgi, Merhawi T.; Fennie, Kristopher P.; Sheehan, Diana M.; Ibrahimou, Boubakari; Jones, Sandra G.; Brock, Petra; Ladner, Robert A.; Trepka, Mary Jo
ABSTRACT: The purpose of this study was to assess the prevalence of chlamydia or gonorrhea and factors associated with the diagnoses among people with HIV (PHIV) in the Ryan White Program Part A (RWP) in Miami-Dade County, Florida. We used 2017 calendar year data to identify factors associated with a chlamydia or gonorrhea diagnoses using logistic regression. About 50% of the 7110 PHIV who were ≥18 years old in active Ryan White care in 2017 reported being screened for chlamydia or gonorrhea. Of those screened, 2.3% reported diagnoses of chlamydia, gonorrhea or both. In the adjusted model, compared to PHIV ≥40 years-old, PHIV aged 18–24 and 25–39 years reported higher odds of diagnoses (adjusted odds ratio [aOR] 4.29; 95% confidence interval [CI]: 1.73–10.63 and aOR 4.58; 95% CI; 2.62–7.99 respectively). Those with multiple sexual partners in the last 12 months reported higher odds of diagnoses (aOR 1.67; (95% CI; 1.04–2.69)). Screening rates for chlamydia or gonorrhea are low, relative to CDC guidelines. Interventions are needed to increase rates of screening and targeted behavioral risk reduction techniques are highly recommended among those 18–39 years of age and those who have multiple sexual partners.